2012
DOI: 10.4103/0019-5049.93341
|View full text |Cite
|
Sign up to set email alerts
|

Post-operative pain and analgesic requirements after paravertebral block for mastectomy: A randomized controlled trial of different concentrations of bupivacaine and fentanyl

Abstract: Background:Paravertebral block (PVB) is useful for post-operative analgesia after breast surgery. Bupivacaine is used for PVB at higher concentrations (0.5%), which may lead to systemic toxicity after absorption. Therefore, we proposed to evaluate the efficacy of lower concentrations of bupivacaine with and without fentanyl for thoracic PVB in patients undergoing surgery for carcinoma breast.Methods:Forty-eight patients scheduled for surgery for breast cancer were enrolled in this prospective, randomized, doub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 21 publications
0
18
2
Order By: Relevance
“…Reported studies[252627282930] shows different results on pain management and the difference in the results from our study could possibly be because of the difference in the nature of surgery, kind and dose of drugs, and the difference in the method of treatment.…”
Section: Discussioncontrasting
confidence: 60%
“…Reported studies[252627282930] shows different results on pain management and the difference in the results from our study could possibly be because of the difference in the nature of surgery, kind and dose of drugs, and the difference in the method of treatment.…”
Section: Discussioncontrasting
confidence: 60%
“…Karakaya et al and Sert et al demonstrated prolongation of motor and sensory block as well as statistically significant increases in analgesic duration when fentanyl was added to bupivacaine [ 35 ] or articaine [ 36 ] axillary blocks without epinephrine. Bhuvaneswari et al found that addition of fentanyl to 0.25% bupivacaine plus epinephrine paravertebral blocks prolonged analgesia to 18 hours, which was comparable to the duration of blocks with 0.5% bupivacaine plus epinephrine [ 37 ]. Finally, Sindjelic et al were recently able to show an improvement in quality and duration of mixed bupivacaine/lidocaine cervical plexus blocks for carotid endarterectomy surgery [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…The techniques like paravertebral block, brachial plexus block by infraclavicular approach have been tried for postoperative analgesia following mastectomy. [ 10 11 12 ] Arunakul and Ruksa[ 13 ] found that single injection of paravertebral block (PVB) reduced pain scores and opioid consumption in MRM. However, these techniques are laborious and technically challenging.…”
Section: Discussionmentioning
confidence: 99%